The pH Level Influence on Hydroxyapatite Phase Composition Synthesized with Hydrothermal Method; IOP Conference Series: Materials Science and Engineering; Vol. 731 : Advanced Materials for Engineering and Medicine (AMEM-2019) - Chuprunov K.; Yudin A.; Lysov D.; Kolesnikov E.; Kuznetsov D.; Leybo D.; Ilinykh I.; Godymchuk (Godimchuk) A. Yu. Anna Yuryevna (2020, 2020)
Title screen